Crypt archaeology after Spitalfields : dealing with our recent dead - Cox, Margaret
A decade ago, the crammed burial-vaults under Christ Church, Spitalfields, a fine English Baroque church in east-central London designed by Hawksmoor, were archaeologically excavated. This pioneering work in the post-medieval archaeology of our own culture's burial practice has not been followed up. Why?